ChemInform Abstract: Copper‐Catalyzed Domino Synthesis of 2‐Arylthiochromanones Through Concomitant C—S Bond Formations Using Xanthate as Sulfur Source. Issue 18 (April 2016) - Sangeetha, Subramani; Muthupandi, Pandi; Sekar, Govindasamy
Abstract: This domino process proceeds through Cu‐catalyzed C(aryl)—S bond formation by coupling of xanthate with 2‐iodochalcones followed by thioester C—S bond cleavage and subsequent S—C bond formation via intramolecular Michael addition.